Discrete fractional solutions to the k-hypergeometric differential equation - Yilmazer, Resat; Ali, Karmina (Wiley, 2021)
In this study, the discrete fractional nabla calculus operator is used to investigate the k-hypergeometric differential equation for both homogeneous and nonhomogeneous states. To solve the guiding equation, we implement certain classical transformations and also constrain the parameters needed to determine them valued. In order to achieve these results, some equipment like the Leibniz rule, the index law, the shift operator, and the power rule are set out in the frame of the discreet fractional calculus. We use all of these tools to the governing equation for homogeneous and nonhomogeneous situations. The major benefit of the fractional nabla operator is that it implements singular differential equations and converts them into fractional order equations. As a result, several new exact fractional solutions of the given equation are constructed.
Keywords: discrete fractional; nabla operator; k-hypergeometric differential equation